The Green Deal - dynamizer of digitalization in tourism: The case of Cluj-Napoca smart city - Delia Popescu; Monica Maria Coroş; Iuliana Pop; Cristina Bolog (Amfiteatru Economic Journal, 2022)
Global tourism activity reached high levels before the outbreak of the pandemic, but it was also one of the most affected economic sectors in 2020 when there was a real collapse of tourism activity. Tourism is an activity with a high degree of pollution, with many studies highlighting the fact that the hotel industry is a high-energy consumption and polluting sector. The Green Deal (GD), a bold project of the European Union, aims to make Europe carbon-neutral by 2050. Tourism is not an objective explicitly presented in the GD but because tourism is an activity with a high degree of pollution it must align to the new requirements. Targeting the hotel market of Cluj-Napoca, the article aims to analyse the activity of the hotels in terms of their adaptation to the new recommendations of the European Commission, implementing the GD, and moving to digitalization, as a new stage, for a cleaner environment. The research combines descriptive and inferential statistical methods to test the hypotheses formulated and to investigate the links between the variables studied, through unifactorial one-way ANOVA analysis. At the same time, the internal consistency of the 62 items of the questionnaire, filled in by the 38 hotels participating in the study, was analysed, obtaining a high Cronbach-Alpha score (0.88). The main conclusions drawn indicate a low degree of familiarity of hotel employees with the provisions of GD. In addition, especially in the case of internationally affiliated and of 4- and 5-star (*) hotels, the existence of a sustainable development policy is associated with a focus on local producers for both the supply of agri-food products and cosmetics and personal care products. The COVID-19 pandemic accelerated the digitization process of Cluj-Napoca hotels.
Keywords: Q20; Q30; Q53; Z30; 330; Green Deal (GD); tourism; digitalization; smart city